A Pd–TSH composite membrane reactor for one-step oxidation of benzene to phenol. Issue 54 (12th June 2019) - Liu, Wei; Wang, Xiaobin; Zhao, Rongrong; Meng, Bo; Zuo, Cuncun; Tan, Xiaoyao
Abstract : A Pd–TSH membrane shows excellent stability and outstanding performance for phenol production in the one-step oxidation of benzene to phenol. Abstract : Pd membranes with excellent stability and flux were prepared by modified electroless plating, and a loose TSH zeolite with intraparticle hollows was joined on the Pd membrane by a covalent bonding method. The prepared Pd–TSH composite membrane shows outstanding performance for phenol production in the one-step oxidation of benzene to phenol.